2010
DOI: 10.1007/s12161-010-9165-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extraction Methods for Efficient Detection of Enteric Viruses in Pork Meat Products

Abstract: We report an in-house protocol for extraction and purification of nucleic acids of enteric viruses, which gives more consistent results than representative commercial methods. The protocol uses 4 M guanidine thiocyanate, 0.5% N-lauroylsarcosine sodium salt, and 25 mM sodium citrate pH 7.0 supplemented with 0.14 M β-mercaptoethanol for lysis of virus particles. The addition of TRIzol followed by chloroform-based separation of the aqueous phase is used to purify nucleic acids from the lysate. RNA precipitation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The presence of guanidine thiocyanate which lyses the cells and inactivates RNases, as well as phenol, which denaturates proteins, within the TRI Reagent® Solution (Stals et al, 2011) may explain the efficient cell lysis. This finding is in accordance with other studies, which demonstrated that TRIzol® (a similar agent like TRI Reagent® Solution) is suitable for virus recovery especially from internally contaminated pork meat (Martinez-Martinez et al, 2011;Sair et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…The presence of guanidine thiocyanate which lyses the cells and inactivates RNases, as well as phenol, which denaturates proteins, within the TRI Reagent® Solution (Stals et al, 2011) may explain the efficient cell lysis. This finding is in accordance with other studies, which demonstrated that TRIzol® (a similar agent like TRI Reagent® Solution) is suitable for virus recovery especially from internally contaminated pork meat (Martinez-Martinez et al, 2011;Sair et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…For meat products like liver sausages, protocols using manual elimination of fat, disruption in phosphatebuffered saline (PBS), centrifugation and column-based RNA extraction (Colson et al, 2010), disruption using stomacher, centrifugation, polyethylene glycol (PEG) precipitation, chloroform-butanol treatment and bead-based RNA extraction (Martin-Latil et al, 2014), or disruption in TRI ® Reagent using stomacher, chloroform-butanol treatment and bead-based RNA extraction (Szabo et al, 2015) have been described. Systematic comparisons of the different methods by independent laboratories have not been published, although limited comparative studies on the efficiency of selected methods are available (Martinez-Martinez et al, 2011;Martin-Latil et al, 2014;Szabo et al, 2015). Reported detection limits of the methods are 2.9 9 10 3 HEV genome copies per 5 g raw sausage (Szabo et al, 2015), 5.3 9 10 4 HEV genome copies per 2 g liver sausage (Szabo et al, 2015) and 8.7 9 10 3 to 8.7 9 10 4 HEV genome copies per 3 g figatelli or liver sausage (Martinelli et al, 2015).…”
Section: Methods For Virus and Rna Extraction From Food And Watermentioning
confidence: 99%
“…Shellfish have been considered as a major source of food-borne viruses due to their filter-feeding mechanism that can concentrate virus from polluted waters (Carter, 2005). Pork meat products are also a significant route of zoonotic transmission, as enteric viruses can infect humans from the consumption of contaminated raw or undercooked pork meat (Martínez-Martínez et al, 2011). …”
Section: Introductionmentioning
confidence: 99%